Pengaruh Aliran Gas Nitrogen Pada Karakteristik Listrik Film Gan Yang Ditumbuhan Di Atas Substrat Silikon (111) Dengan Teknik Sol Gel Spincoating - R. Tayubi, Yuyu; Rusdiana, Dadi (BERKALA FISIKA, 2010)
GaN thin films have been successfully grown on silicon substrate (111) by sol gel technique spincoating with nitrogen gas flow variation. GaN films were characterized using X-ray diffraction, SEM and electrical characteristics. The results showed that the film has a polycrystalline structure, while the electrical characterization of resistivity measurements on several samples of GaN films with the variation of N2 gas flow rate showed that the electrical resistivity of films decreased when the rate of N2 gas flow is increased. Keywords: GaN, sol gel spincoating, resistivity.